Perspectives on translation of positronium imaging into clinics - Moskal, Pawel; Stępień, Ewa Ł. (Frontiers in Physics, 2022)
Positronium imaging is a newly invented diagnostic method with promising potential to improve specificity in the assessment of tissue pathology in-vivo at the molecular level, based on information available from the data collected by the upcoming generation of multi-photon (multi-gamma) PET systems. The image of positronium properties created in the patient’s body during PET examination tells about the inter- and intra-molecular structure of the tissue and the concentration of bio-active molecules in the tissue. In this communication, we advocate the opinion that total-body PET systems, thanks to their high imaging sensitivity and high time resolution, open up the prospect of translating positronium imaging into clinics.